Defiance to permanence and acceptance agenda in professional master's degree - Vieira, Karen Mariane Petry Welter (2023)
The present study was focused to the permanence conditions of working-researchers, in the area of post-graduation - Professional Master’s Degree. It was used a narrative qualitative study, concerning sociocultural aspects, that aimed to comprehend the defiance within the academic course, It was highlight that the challenges throughout the formative course as the overlapped chores referred to the formation and working activities, and the social withdraw caused by Covid-19. As permanence indicators, it was identified the personal and social mobilization of the researchers, and the program’s profile focused on the working people. Thus, it was highlighted the necessity to consolidate an acceptance policy, capable of driving a range of actions to strengthen the formative course.